Pulmonary artery banding for univentricular heart beyond the neonatal period. (July 2014) - Sasikumar, Navaneetha; Ramanan, Sowmya; Rema, Krishna Manohar Soman; Subramanyan, Raghavan; Kumar, Raghavannair Suresh; Cherian, Kootturathu Mammen
Background: It is standard practice to band the pulmonary artery at 2 to 4 weeks of age in patients with univentricular hearts with increased pulmonary blood flow. The behavior of patients banded beyond the neonatal period has not been well elucidated. Patients and methods: This was a retrospective chart review of 32 consecutive patients (one neonate) who underwent pulmonary artery banding for functionally univentricular heart. The mean age at banding was 5.7 ± 6.0 months, and 34.4% were over 6-months old. Results: Mortality was 15.6%. The mean systolic pulmonary artery pressure decreased from 43.6 ± 9.7 to 29.6 ± 7.0 mm Hg. The mean pre-discharge echocardiographic band gradient was 60.6 ± 13.6 mm Hg (mean systemic systolic pressure 73.7 ± 11.0 mm Hg) and systemic oxygen saturation was 81.7% ± 5.8%. At a mean follow-up period of 44.9 ± 30.0 months, 6 patients were lost to follow-up, 13 had undergone bidirectional Glenn shunt, and 7 had Fontan operations. Pulmonary artery mean pressure was 17.2 ± 4.6 mm Hg at pre-Glenn catheterization. Of the 5 patients who had not undergone further surgery, only one was inoperable. All were in functional class I or II. Conclusion: Pulmonary artery banding beyond the neonatal period in suitable patients with univentricular hearts provides reasonable palliation in the intermediate term, with a significant number successfully undergoing Fontan stages.